2012
DOI: 10.1051/alr/2012021
|View full text |Cite
|
Sign up to set email alerts
|

Comparing selectivity of a standard and turned mesh T90 codend during towing and haul-back

Abstract: -In this study, we compared the size selectivity of a T 90 codend (netting turned by 90 degrees) with that of a standard codend made of similar netting. Sea trials were conducted in a Norway lobster directed fishery in the KattegatSkagerrak area, where there is a need for improved selectivity because of a severe discard problem. The codends were tested by fishing simultaneously with them in a twin trawl rig. Codend covers mounted with Minisamplers were used, which made it possible to catch individuals escaping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 33 publications
(36 reference statements)
1
42
1
Order By: Relevance
“…The sequence of analysis described above was implemented in the SELNET software tool , which was used for all analyses. SELNET has previously been applied to analyze size-selectivity data (Sistiaga et al 2010;Frandsen et al 2011;Wienbeck et al 2011Wienbeck et al , 2014Eigaard et al 2012;Herrmann et al 2012Herrmann et al , 2013aHerrmann et al , 2013bHerrmann et al , 2013cHerrmann et al , 2013dHerrmann et al , 2015Madsen et al 2012;Krag et al 2014a;Tokac et al 2014;Sala et al 2015) and catch comparison data (Krag et al 2014b) collected with trawls. This is the first time this method was used to analyze catch data of fishing gears such as boat seines and surrounding nets.…”
Section: Catch Performance Of a Surrounding Netmentioning
confidence: 99%
“…The sequence of analysis described above was implemented in the SELNET software tool , which was used for all analyses. SELNET has previously been applied to analyze size-selectivity data (Sistiaga et al 2010;Frandsen et al 2011;Wienbeck et al 2011Wienbeck et al , 2014Eigaard et al 2012;Herrmann et al 2012Herrmann et al , 2013aHerrmann et al , 2013bHerrmann et al , 2013cHerrmann et al , 2013dHerrmann et al , 2015Madsen et al 2012;Krag et al 2014a;Tokac et al 2014;Sala et al 2015) and catch comparison data (Krag et al 2014b) collected with trawls. This is the first time this method was used to analyze catch data of fishing gears such as boat seines and surrounding nets.…”
Section: Catch Performance Of a Surrounding Netmentioning
confidence: 99%
“…The T90 codend, in which the standard diamond mesh netting orientation is turned 90°, is known to have the potential to improve size selectivity properties compared to the conventional diamond mesh codend made of the same netting (Madsen, Herrmann, Frandsen, & Krag, ). An experiment reported by Dahm () and based on an idea proposed by Moderhak (), indicated that a turned mesh codend could improve the size selection considerably in a diamond mesh codend (Wienbeck, Herrmann, Moderhak, & Stepputtis, ), and thus provide a more open mesh that might permit more small individuals to escape (Madsen et al., ). Therefore, the use of T90 netting for trawl codends may be an alternative design to potentially satisfy both fisheries management and fishermen (Tokaç et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The T90 codend has been the focus of increased scientific interest in recent years in northern European fisheries (Arkley, ; Hansen, ; Herrmann, Priour, & Krag, ; Herrmann, Wienbeck, Moderhak, Stepputtis, & Krag, ; Madsen et al., ; Wienbeck et al., ), and was introduced in 2006 into the legislation (EU Regulation no. 2187/2005) for the Baltic Sea cod ( Gadus morhua ) fishery (Herrmann et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple technique that has been shown to improve trawl selectivity is modifying the size and configuration of the cod end mesh (Perez-Comas et al 1998;He 2007;Madsen and Valentinsson 2010). Recent studies have focused on the development and use of T90-mesh cod ends (Digre et al 2010;Wienbeck et al 2011Wienbeck et al , 2014Madsen et al 2012;Herrmann et al 2013Herrmann et al , 2015Bayse et al 2016). The T90 mesh is conventional diamond mesh that has been turned 90°in orientation; this configuration allows the meshes over the entire cod end to remain more open than those of diamond-mesh cod ends, thereby improving size-selection characteristics (Herrmann et al 2007).…”
mentioning
confidence: 99%